Consumer Personality and Green Buying Intention: The Mediate Role of Consumer Ethical Beliefs - Lu, Long-Chuan (Journal of business ethics, 2015)
The primary purpose of this study is to link the effects of consumer personality traits (antecedents) on green buying intention (consequences) via the mediating variable of consumer ethical beliefs so as to extend the context of green buying intentions with consumer ethics literatures. Based on a survey of 545 Taiwanese respondents, consumer personality traits were found to significantly affect consumer ethical beliefs. The results also indicate that some dimensions of consumer ethical beliefs significantly predict consumer intention to buy green products. Generally speaking, this study enhances our knowledge of consumers’ ethical decision-making in the context of green consumption behaviors. Theoretical and managerial implications, limitations, and future research are also provided.